FRI0274 Hydroxychloroquine down-regulates interferon-alfa elevation through tlr-9 recognition of nucleotides which is irresponsive to glucocorticoid. (23rd January 2014) - Jin, O.; Zhang, X.; Fang, L.; Li, Q.; Huang, H.; Wei, Q.; Lin, Z.; Liao, Z.; Lin, D.; Gu, J.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by chronic stimulation of the innate immune system by endogenous nucleic acids, which results in the activation of interferon-αlfa (IFN-α) pathway. Glucocorticoid have been widely used to treat autoimmune diseases due to their strong anti-inflammatory effects, however, a recent research has found that toll-like receptors (TLRs) recognition of self nucleic acids hampers the effects of glucocorticoid in lupus. Hydroxychloroquine has been found to block the TLRs, though its special mechanisms are still unknown. Objectives: We want to evaluate whether glucocorticoid and/or hydroxychloroquine influence the induction of IFN-α through TLR-9 recognition of nucleotides in human peripheral blood mononuclear cells (PBMCs), and whether hydroxychloroquine could improve the effects of glucocorticoid in lupus. Moreover, we want to know whether hydroxychloroquine influences signal proteins in the TLR pathway. Methods: Freshly isolated PBMCs of healthy donors were stimulated with the TLR-9 agonist, CpG oligodeoxynucleotides (CpG-A ODN)-2216, then treated with hydroxychloroquine and/or different doses of glucocorticoid (hydrocortisone: low dose (10 -5 M), median dose (10 -4 M), high dose (10 -3 M)). The changes in the expression of IFN-α and signal proteins (MyD88, AP-1, IKK-α) in PBMCs were detected by real time PCR. Results: (1) Hydroxychloroquine significantly reversed the elevation of IFN-α caused by ODN 2216 (p=0.033<0.05), and in different doses of glucocorticoid (low dose: p=0.028, median dose: p=0.025, high dose: p=0.011). (2) The glucocorticoid had no effects on the IFN-α expression in PBMCs with or without ODN 2216 stimulation (control: F=1.677, p=0.248; ODN2216: F=1.406, p=0.31). (3) Hydroxychloroquine had no effects on the expression of MyD88, AP-1, IKK-α in PBMCs with or without ODN 2216 stimulation, in different doses of glucocorticoid ((MyD88: none of glucocorticoid: F=4.938, p=0.054; low dose: F=2.182, p=0.194; median dose: F=1.406, p=0.316, high dose: F=1.15, p=0.378), (AP1: none of glucocorticoid: F=0.285, p=0.762; low dose: F=0.787, p=0.497; median dose: F=5.053, p=0.052, high dose: F=0.0911, p=0.451), (IKK-α: none of glucocorticoid: F=1.367, p=0.324; low dose: F=1.273, p=0.346; median dose: F=0.951, p=0.438, high dose: F=0.819, p=0.485)). Conclusions: (1) Hydroxychloroquine hampers the critical pathogenesis of lupus that TLR-9 recognition of nucleotides elevates the IFN-α expression in PBMCs. (2) The combination with hydroxychloroquine seems to be a good choice to help glucocorticoid to achieve a better disease control by inhibiting IFN-α, which is irresponsive to glucocorticoid alone. (3) Hydroxychloroquine does not significantly influence signal proteins (MyD88, AP-1, IKK-α) in the TLR pathway, which implies its weak influence in innate immunity. Acknowledgements: This study was supported by the grant for the scientific research foundation of ministry of education in China (20090171120090). Disclosure of Interest : None Declared